2006
DOI: 10.1523/jneurosci.2481-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Training Alters Object Representations in Human Extrastriate Cortex

Abstract: Visual object recognition relies critically on learning. However, little is known about the effect of object learning in human visual cortex, and in particular how the spatial distribution of training effects relates to the distribution of object and face selectivity across the cortex before training. We scanned human subjects with high-resolution functional magnetic resonance imaging (fMRI) while they viewed novel object classes, both before and after extensive training to discriminate between exemplars withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
250
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(277 citation statements)
references
References 55 publications
22
250
4
1
Order By: Relevance
“…In a recent study (49), we found that 10 h of training on a novel object category produces a nearly 2-fold response to trained compared with untrained categories in some voxels in the ventral visual pathway, which was not present before training. Similarly, neurophysiological studies in nonhuman primates have found that training on discrimination and recognition of visual objects can lead to changes in the selectivity of neural responses in the inferior temporal cortex, a region critical for object recognition (50,51).…”
Section: Discussionmentioning
confidence: 67%
“…In a recent study (49), we found that 10 h of training on a novel object category produces a nearly 2-fold response to trained compared with untrained categories in some voxels in the ventral visual pathway, which was not present before training. Similarly, neurophysiological studies in nonhuman primates have found that training on discrimination and recognition of visual objects can lead to changes in the selectivity of neural responses in the inferior temporal cortex, a region critical for object recognition (50,51).…”
Section: Discussionmentioning
confidence: 67%
“…First, could high-level visual areas simply be selective for shape characteristics? In support of this view, unfamiliar artificial-object categories and relatively simple patterns elicit selective responses in the object-and face-selective cortex in humans 94,95 (FIG. 4).…”
Section: Basic Properties In the Ventral Visual Cortexmentioning
confidence: 85%
“…The pattern of selectivity is distributed and weak in individual voxels, at least for the unfamiliar-object classes that have been tested. For example, in a recent study with high spatial resolution, in the scattered regions that showed the most selectivity the strength of the regions' response to their least-preferred novel objects was approximately two thirds of the response to a preferred novel object 95 . By contrast, the maximum selectivity for some familiar objects is far stronger, even at lower spatial resolution: the FFA, the PPA and the EBA all respond at least two to three times more strongly to their preferred object class (faces, houses and bodies, respectively) than to a wide range of nonpreferred object classes 21 .…”
Section: Basic Properties In the Ventral Visual Cortexmentioning
confidence: 95%
See 1 more Smart Citation
“…On the one hand, experience must surely play some instructive role in the development of face areas, given the ample evidence that neurons in the ventral visual pathway are tuned by experience (Baker et al 2002;Op de Beeck et al submitted). Evidence of such experiential tuning of face perception, in particular, is seen in the 'other race effect', in which behavioural performance (Malpass & Kravitz 1969;Meissner & Brigham 2001) and neural responses (Golby et al 2001) are higher for faces of a familiar than an unfamiliar race, even if the relevant experience occurs after age 3 (Sangrigoli et al 2005).…”
Section: Open Questionsmentioning
confidence: 99%